Intracellular acidosis via activation of Akt-Girdin signaling promotes post ischemic angiogenesis during hyperglycemia. (15th February 2019) - Zhang, Hong-Ming; Liu, Mo-Yan; Lu, Jun-Xiu; Zhu, Mo-Li; Jin, Qun; Ping, Song; Li, Peng; Jian, Xu; Han, Ya-Ling; Wang, Shuang-Xi; Li, Xiao-Yan
Abstract: Aims: The impaired angiogenesis is the major cause of diabetic delayed wound healing. The molecular insight remains unknown. Previous study has shown that high glucose (HG) activates Na + /H + exchanger 1 (NHE1) and induces intracellular alkalinization, resulting in endothelial dysfunction. The aim of this study is to investigate whether activation of NHE1 in endothelial cells by HG damages the angiogenesis in vitro and in vivo. Methods and results: We used western blot to detect the phosphorylations of both Akt and Girdin, and pH-sensitive BCECF fluorescence to assay NHE1 activity and pHi value, respectively. The angiogenesis was evaluated by measuring the number of tube formation in vitro, and blood perfusion by laser doppler and neovascularization by staining CD31 in vivo. Our results indicated that induction of intracellular acidosis (IA) increased p-Akt and p-Girdin in human umbilical vein endothelial cells (HUVEC). HG activated NHE1 and increased pHi value in a time-dependent manner, associated with the decreased phosphorylations of both Akt and Gridin, while inhibition of NHE1 by amiloride abolished the HG-induced reductions of p-Akt and p-Girdin. However, silence of Akt by siRNA transfection or pharmacological inhibitors (wortmannin and LY294002) bypassed IA-induced Girdin phosphorylation. Overexpression of constitutively active Akt abolished HG-reduced Girdin phosphorylation. In addition, upregulation of Akt or inhibition of NHE1 remarkably attenuated HG-impaired tube formation in HUVEC. In vivo study revealed that amiloride dramatically rescued hyperglycemia-delayed blood perfusion and neovascularization by augmenting ischemia-induced angiogenesis. Conclusion: IA promotes ischemia-induced angiogenesis via Akt-dependent Girdin phosphorylation in diabetic mice. Highlights: Intracellular acidosis activated Akt in endothelial cells. Hyperglycemia inhibits endothelial cell-mediated angiogenesis and the delayed recovery of blood perfusion in mice following hind limb ischemia through Akt dephosphorylation mediated by NHE1/pHi in vivo.